Tutela jurisdiccional del derecho a vivir sin violencia de género - Ramírez Figueroa, Jim L. (2019)
With the enforcement of Law 30364, the Peruvian State complies with adapting national legislation to the parameters set by the Inter-American Convention to Prevent, Punish and Eradicate Violence against Women (Convention of Belém do Pará). In this context, the present work critically analyzes whether protection orders constitute a simple, fast and effective remedy against gender violence. To this end, it is reasoned about the fundamentals and nature of the protection orders, as well as the probative activity necessary for its granting. From this, it is affirmed that the guardianship granted by the protection orders is a preventive inhibitory guardianship.